ENVIRONMENTAL FRAGILITY TO EROSIVE PROCESSES IN HYDROGRAPHIC BASINS: THE EVENT ON NEGRINHA RIVER IN OSVALDO CRUZ - SP - Cardoso, Everton Henrique Goncales [UNESP]; Moroz Caccia Gouveia, Isabel Cristina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
The present study has identified environmental fragility levels along the high Negrinha River basin (Osvaldo Cruz and Parapua / SP) to erosive processes and, reliableresults have encouraged environmental education actions. Proposed by Ross (1994), gauging the impact of frailty was the result of intersection of cartographic by-products of surface curvature, terrain slope, different soil types and land use and coverage. To accomplish this, the fragility map's production was performed on ArcGIS 10.3 software, with field validation in nineteen catchments of the basin. The study reveals the predominance of medium and strong environmental weaknesses presented in 49.81% and 43.25% of the area, respectively. The identification of erosion risk mapping should address policy adoption, directly to promote sustainable land management both for agricultural activity and for the expansion of urbanization, and the approach of protected areas.
Keywords: Environmental Fragility; Erosive Processes; River Basin